2017
DOI: 10.1186/s13104-017-3080-0
|View full text |Cite
|
Sign up to set email alerts
|

External quality assessment of malaria microscopy diagnosis among public health facilities in West Amhara Region, Ethiopia

Abstract: ObjectiveTo evaluate the importance of external quality assessment program on malaria microscopic diagnosis.ResultsA total of 3148 slides were collected in 4 consecutive external quality assessment rounds and blindly rechecked at Amhara Public Health Institute. The average agreement between health facility and APHI slide readers was 96.6%. The percent agreement for parasite detection and species identification for P. falciparum became improved in four consecutive EQA rounds from 93.88 to 99.24% and 92.67 to 97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 7 publications
7
16
5
Order By: Relevance
“…Therefore, laboratories should identify and report species correctly. The proportion of species mis-diagnosis in the present study (5.4%) goes in line with previous results of 3.4% in the same study area [12] and it is much lower than previous studies from Hawassa [15] and Oromia [14] where the laboratory professionals correctly identified the species in 74.3% and 44.6% of malaria positive slides during panel testing, respectively. The discrepancy might be due to difference in the method of assessment and the status of EQA and other supportive activities from reference laboratories.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, laboratories should identify and report species correctly. The proportion of species mis-diagnosis in the present study (5.4%) goes in line with previous results of 3.4% in the same study area [12] and it is much lower than previous studies from Hawassa [15] and Oromia [14] where the laboratory professionals correctly identified the species in 74.3% and 44.6% of malaria positive slides during panel testing, respectively. The discrepancy might be due to difference in the method of assessment and the status of EQA and other supportive activities from reference laboratories.…”
Section: Discussionsupporting
confidence: 91%
“…This was due to political instability in areas where respective health laboratories are located. The mean test agreement in detecting malaria parasites in the present study (97.31%) was in line with previous results from Amhara region of Ethiopia (96.6%) [12], and Pakistan (99.0-99.5%) [13]. On the other side the test agreement was higher than recent results of 78%, 88% and 91.7% from Oromia region of Ethiopia [14], Hawassa [15] and Addis Ababa [16], respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It also shows the impact of EQA on malaria microscopy performance of health laboratories. A similar study conducted in west Amhara before 5 years revealed a mean test agreement of 96.6% with 2.63, 0.7 and 3.4% of re-checked slides reporting false positive, false negative and species mis-diagnosis results, respectively [11]; however the results might not be consistent as there is difference in laboratory staff (due to turnover and recruitment), training, patient flow, quality of supplies and test procedures. Therefore, the aim of the present study was to show the recent 2 years malaria microscopy performance of public health facility laboratories in west Amhara region as assessed through blind rechecking.…”
Section: Introductionmentioning
confidence: 90%
“…In the absence of differential diagnosis such as access to blood cultures or PCR to rule out causes of clinical symptoms at many public health facilities in endemic areas, especially in young children, untreated P. falciparum malaria can progress rapidly to severe and life-threatening forms of the disease [31]. This can lead to deaths and undermine both the clinical confidence and credibility of health services if patients who might have malaria but are not treated and the cause of symptoms for the hospital visit is not identified [32]. Additionally, untreated cases can contribute to the transmission of malaria in an area [33].…”
Section: Discussionmentioning
confidence: 99%